(-9x+4)-6=8(x-3)

Simple and best practice solution for (-9x+4)-6=8(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-9x+4)-6=8(x-3) equation:


Simplifying
(-9x + 4) + -6 = 8(x + -3)

Reorder the terms:
(4 + -9x) + -6 = 8(x + -3)

Remove parenthesis around (4 + -9x)
4 + -9x + -6 = 8(x + -3)

Reorder the terms:
4 + -6 + -9x = 8(x + -3)

Combine like terms: 4 + -6 = -2
-2 + -9x = 8(x + -3)

Reorder the terms:
-2 + -9x = 8(-3 + x)
-2 + -9x = (-3 * 8 + x * 8)
-2 + -9x = (-24 + 8x)

Solving
-2 + -9x = -24 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-2 + -9x + -8x = -24 + 8x + -8x

Combine like terms: -9x + -8x = -17x
-2 + -17x = -24 + 8x + -8x

Combine like terms: 8x + -8x = 0
-2 + -17x = -24 + 0
-2 + -17x = -24

Add '2' to each side of the equation.
-2 + 2 + -17x = -24 + 2

Combine like terms: -2 + 2 = 0
0 + -17x = -24 + 2
-17x = -24 + 2

Combine like terms: -24 + 2 = -22
-17x = -22

Divide each side by '-17'.
x = 1.294117647

Simplifying
x = 1.294117647

See similar equations:

| 7x-35+6x+18=22 | | a-3%4=2%3 | | -8x=-152 | | 1.87p=149600 | | 133=(3x+1)(x+1) | | 18+9/8r=-18 | | y-9/x=5/7 | | 1/10(y-6)=25(y+8)-1/5y | | 1/4+3x/8+3/16=5/8 | | 4.50+14.40=9 | | X-(-10)=-3 | | 9x-(4x-10)=2 | | 4.7+5.2x-0.4x=-4.9 | | -20x+6=5x | | V/-2=8 | | 4+9+5+x=16 | | 3x+2-6x=-1x-15x+8-5x | | -(6x-6)-(-5x+9)=-4 | | 7x-35+6x+8=22 | | 7-9x-3=-74+4x-13 | | 7r=-3.5 | | -2/3t=2 | | 14-3/7x=5 | | t^2+36=0 | | 3x+12=2x-4 | | 0.41x+0.72=0.61x-4.22 | | h+4=30 | | x(2x-8)=(2x+5)(x-6) | | 6y=-17 | | (4x+34)+(7x-10)+(5x+12)=180 | | v^2-3v-40=0 | | 60(10-x)=90 |

Equations solver categories